2011
DOI: 10.1111/j.1365-2109.2010.02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotifer enrichment with herbal extracts on growth and resistance of red sea bream, Pagrus major (Temminck & Schlegel) larvae against Vibrio anguillarum

Abstract: The e¡ects of the dietary medicinal herbs Massa medicata, Crataegi fructus (Cf), Artemisia capillaries, Cnidium o⁄cinale and their mixture (HM), on growth and resistance againstVibrio anguillarum were examined using larval red sea bream, Pagrus major. The methanol extracts of Cf and HM inhibited the proliferation of seven infectious bacterial strains including the genera Aeromonas, Edwasiella, Photobavterium, Pseudomonas and Vibrio. Rotifers enriched with emulsi¢ed bonito oil containing extracts of Cf and HM l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…A mixture of equal proportions of six herbs and plant materials in diets enhanced or impaired enzyme activity (Lin et al, 2006). A diet of rotifer enriched with a herbal mixture of Massa medicata, Crataegi fructus, Artemisia capillaries, and Cnidium officinale promoted growth and resistance against Vibrio anguillarum in red sea bream (Pagrus major) larvae (Takaoka et al, 2011). The plant mixture basil flowers and commercial antiviral plants (VPH®, HSV®, Amazonas Herbs Distrito Federal, Mexico) provided protection for whiteleg prawns (Litopenaeus vannamei) against WSSV (Peraza-Gómez et al, 2009.…”
Section: Administration and Application Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A mixture of equal proportions of six herbs and plant materials in diets enhanced or impaired enzyme activity (Lin et al, 2006). A diet of rotifer enriched with a herbal mixture of Massa medicata, Crataegi fructus, Artemisia capillaries, and Cnidium officinale promoted growth and resistance against Vibrio anguillarum in red sea bream (Pagrus major) larvae (Takaoka et al, 2011). The plant mixture basil flowers and commercial antiviral plants (VPH®, HSV®, Amazonas Herbs Distrito Federal, Mexico) provided protection for whiteleg prawns (Litopenaeus vannamei) against WSSV (Peraza-Gómez et al, 2009.…”
Section: Administration and Application Methodsmentioning
confidence: 99%
“…The extract processes are simple . The extraction can be done with acetone (Punitha et al, 2008), benzene (Balasubramanian et al, 2008;Punitha et al, 2008), butanol (Praseetha, 2005;Punitha et al, 2008), ethanol (Adigüzel et al, 2005;Harikrishnan et al, 2011c;Hwang et al, 2013;Sudhakaran et al, 2006;Wang et al, 2011), ethyl acetate (Abutbul et al, 2004), methanol (Adigüzel et al, 2005;Balasubramanian et al, 2007;Citarasu et al, 2003), hexane (Adigüzel et al, 2005), petroleum ether (Balasubramanian et al, 2007;Punitha et al, 2008;Sudhakaran et al, 2006), diethyl ether, chloroform, ethyl acetate (Balasubramanian et al, 2007), or even boiling in hot water (Immanuel et al, 2010), boiling in water and then fermented by yeasts (Takaoka et al, 2011).…”
Section: Sources Of Medicinal Plantsmentioning
confidence: 97%
See 2 more Smart Citations
“…Besides, it has been demonstrated that factors such as species, age, size and stress determine the appropriate usage of plant dietary supplements 50 . Further several herbal supplements are reported to stimulate appetite and enhance weight gain when they are incorporated to cultured fish [51][52][53] . It is hypothesized that higher dosage of herbal diet supplements has resulted in stimulation of enzyme inhibitors, as most plants contain inhibitors to protect their major components from accidental degradation 54 .…”
Section: Discussionmentioning
confidence: 99%